Polyolefin reweaved ultra-micropore membrane for CO2 capture - Xiuling Chen; Guining Chen; Cong Xie; Lei Wu; Gongping Liu; Nanwen Li; Wanqin Jin (Nature Communications)
Abstract High-performance gas separation membranes have potential in industrial separation applications, while overcoming the permeability-selectivity trade-off via regulable aperture distribution remains challenging. Here, we report a strategy to fabricate Polyolefin Reweaved Ultra-micropore Membrane (PRUM) to acquire regulable microporous channel. Specifically, olefin monomers are dispersed uniformly into a pristine membrane (e.g., PIM-1) via solution diffusion method. Upon controlled electron beam irradiation, the olefin undergoes a free radical polymerization, resulting in the formation of olefin polymer in-situ reweaved in the membrane. The deliberately regulated and contracted pore-aperture size of the membrane can be accomplished by varying the olefin polymer loading to achieve efficient gas separation. For instance, PIM-1 PRUM containing 27 wt% poly-glycidyl methacrylate demonstrate CO2 permeability of 1976 Barrer, combined with CO2/CH4 and CO2/N2 selectivities of 58.4 and 48.3 respectively, transcending the performance upper bounds. This controllable and high efficiency-design strategy provides a general approach to create sub-nanometre-sized pore-apertures of gas separation membranes with wide universality.